Cascade Effects Induced by Extreme Storms and Floods: The Case of Storm Daniel (2023) in Greece - Diakakis, Michalis; Sarantopoulou, Andromachi; Marilia Gogou; Filis, Christos; Nastos, Panagiotis; Kapris, Ioannis; Vassilakis, Emmanuel; Konsolaki, Aliki; Lekkas, Efthymis (Water, 2025)
The anticipated rise in extreme flood events in the Eastern Mediterranean region indicates an increase in significant societal impacts that have the potential to extend beyond the flooded areas and affect multiple sectors. Despite the criticality of understanding storm and flood risk and how they propagate in modern interconnected societies, the scope and complexity of storm- and flood-triggered cascading effects are still poorly comprehended. This study explores the effects created by the extreme Storm Daniel, occurring in Thessaly, Greece in 2023, aiming to gather new evidence on the types and scale of these cascading effects by analyzing its impacts in the region through fieldwork and official data collection. The results, as a contribution to existing knowledge on cascade effects, provide insights into the nature, the extent, the propagation mechanisms, and the consequences of these triggering events leading to diverse cascade effects. The study identifies the interactions between different phenomena following this extreme storm event to offer a better understanding of how impacts propagate, and therefore a better understanding of future challenges connected with this type of cascading hazards framework, ultimately contributing to predicting and mitigating associated risks.